Wykonywanie kontaktów z dzieckiem w postępowaniu zabezpieczającym - Woś, Paulina (Przegląd Prawno-Ekonomiczny, 2013)
Streszczenie dostępne wyłącznie w jezyku angielskim: Contacts with the child in the proceedings to secure claims In this article, an attempt is made to discuss and evaluate the new rules on the performance of contacts with the child set out in the proceedings to secure claims. The legislator, introducing by the Act of 16 September 2011 (Dz.U. of 2011, No. 233, item. 1381), which entered into force on 3 May 2012, the provision of art. 7562 of the Code of Civil Procedure, makes it possible to ensure the proper performance of the contacts with the child, ruled for the duration of the proceedings by putting the obliged person at the risk of having to pay a certain sum of money for the benefit of the authorized person in the event of breach of the obligations resulting from the decision on the security, concerning the method of contacts with the child ruled by the court. The starting point for discussing the issue in question is the prior analysis of the provisions relating to the performance of contacts.